Constructive Learning Model In Sub Material Music Culture Learning In Madrasah Tsanawiyah 1 Semarang (Universitas Negeri Semarang, 2020)
Based on data analysis can be concluded that the implementation of learning the art of music in class VII A MTs Negeri 1 Semarang using the approach of constructivism run organized, this is evidenced by learning already using model arrests have three stages are (a) presentation of advance organizer, educator provides an overview of the terms of supporting about music (b) the presentation of the material or the learning task, create discussion among students and evaluated by educators and (c) strengthen the cognitive organization, frequently asked questions and a deepening of the material. Learning implemented within 2x45 minutes with the distribution phase advance organizer presentation lasted 15 minutes, the stage presentation of the material or the learning task carried out within 60 minutes, and the stage of cognitive organization strengthen lasted 15 minutes. Suggestions can author to convey, among others: (1) educators should be able to take advantage of instructional media such as musical instruments and projectors which is owned schools maximally.